Sydnone C-4 heteroarylation with an indolizine ring via Chichibabin indolizine synthesis - Albota, Florin; Caira, Mino R.; Draghici, Constantin; Dumitrascu, Florea; Dumitrescu, Denisa E. (Beilstein Journal of Organic Chemistry, 2016)
The synthesis of sydnones heteroarylated at C-4 with an indolizine was achieved by Chichibabin (Tschitschibabin) indolizine synthesis starting from the corresponding sydnone-N-pyridinium bromides. The latter compounds were also transformed to sydnone-indolizines connected through a keto group at the C-4 position by refluxing them in 1,2-epoxybutane with an activated alkyne. The structures of the new compounds were assigned by FTIR, NMR spectroscopy and X-ray analysis.
Keywords: biheteroaryl; Chichibabin synthesis; indolizine; pyridinium N-ylide; sydnone

(untitled) - Alberico, D.; Scott, M. E.; Lautens, M. (Chem. Rev., 2007)

(untitled) - Rossi, R.; Bellina, F.; Lessi, M.; Manzini, C. (Adv. Synth. Catal., 2014)

(untitled) - Stephens, D. E.; Larionov, O. V. (Tetrahedron, 2015)

(untitled) - Hao, W.; Liu, Y. (Beilstein J. Org. Chem., 2015)

(untitled) - Albota, F.; Drăghici, C.; Caira, M. R.; Dumitrascu, F. (Tetrahedron, 2015)

(untitled) - Borrows, E. T.; Holland, D. O. (Chem. Rev., 1948)

Reference Module in Chemistry, Molecular Sciences and Chemical Engineering - Flitsch, W. (Pyrroles with fused six-membered Heterocyclic Rings: (i) a-Fused, 1984)

Heterocyclic Systems with Bridgehead Nitrogen Atoms, Part I - Mosby, W. L. (Fused 5/5 Ring Systems, 1961)

(untitled) - Prostakov, N. S.; Baktibaev, O. B. (Usp. Khim., 1975)

(untitled) - Sharma, V.; Kumar, V. (Med. Chem. Res., 2014)

Fused Five-Membered Hetarenes with One Heteroatom - Shipman, M. (Product Class 16: Indolizines, 2010)

(untitled) - Singh, G. S.; Mmatli, E. E. (Eur. J. Med. Chem., 2011)

(untitled) - Swinborne, P.-J.; Hunt, J. H.; Klinkert, G. (Adv. Heterocycl. Chem., 1979)

(untitled) - Uchida, T.; Matsumoto, K. (Synthesis, 1976)

(untitled) - Kheder, N. A.; Darwish, E. S.; Dawood, K. M. (Heterocycles, 2009)

(untitled) - Caira, M. R.; Popa, M. M.; Drăghici, C.; Barbu, L.; Dumitrescu, D.; Dumitrascu, F. (Tetrahedron Lett., 2014)

(untitled) - Dumitrascu, F.; Căproiu, M. T.; Georgescu, F.; Drăghici, B.; Popa, M. M.; Georgescu, E. (Synlett, 2010)

(untitled) - Dumitrascu, F.; Georgescu, E.; Georgescu, F.; Popa, M. M.; Dumitrescu, D. (Molecules, 2013)

(untitled) - Popa, M. M.; Georgescu, E.; Caira, M. R.; Georgescu, F.; Draghici, C.; Stan, R.; Deleanu, C.; Dumitrascu, F. (Beilstein J. Org. Chem., 2015)

(untitled) - Asundaria, S. T.; Pannecouque, C.; De Clercq, E.; Supuran, C. T.; Patel, K. C. (Med. Chem. Res., 2013)

(untitled) - Browne, D. L.; Harrity, J. P. A. (Tetrahedron, 2010)

(untitled) - Dumitraşcu, F.; Drăghici, C.; Dumitreşcu, D.; Tarko, L.; Râileanu, D. (Liebigs Ann./Recl., 1997)

(untitled) - Wentrup, K.; Kvaskoff, D.; Veedu, R. N. (J. Photochem. Photobiol., A, 2015)

(untitled) - Weisner, A. J.; Turnbull, K. (ARKIVOC, 2014)

(untitled) - Dürüst, Y.; Sağırlı, A.; Kariuki, B. M.; Knight, D. W. (Tetrahedron, 2014)

(untitled) - Dumitrascu, F.; Mitan, C. I.; Dumitrescu, D.; Draghici, C.; Caproiu, M. T. (ARKIVOC, 2002)

(untitled) - Tschitschibabin, A. E. (Ber. Dtsch. Chem. Ges., 1927)

(untitled) - Chai, W.; Kwok, A.; Wong, V.; Carruthers, N. I.; Wu, J. (Synlett, 2003)

(untitled) - Dinculescu, A.; Balaban, T.-S.; Balaban, A. T. (Tetrahedron Lett., 1987)

(untitled) - Kulikova, Yu. A.; Surikova, O. V.; Mikhailovskii, A. G.; Vakhrin, M. I. (Chem. Heterocycl. Compd., 2011)

(untitled) - Adachi, S.; Liew, S. K.; Lee, C. F.; Lough, A.; He, Z.; St Denis, J. D.; Poda, G.; Yudin, A. K. (Org. Lett., 2015)

(untitled) - Brown, A. W.; Harrity, J. P. A. (J. Org. Chem., 2015)

(untitled) - Rodriguez, A.; Moran, W. J. (Synthesis, 2009)

(untitled) - Shih, M.-H.; Tsai, C.-H.; Wang, Y.-C.; Shieh, M.-Y.; Lin, G.-L.; Wei, C.-Y. (Tetrahedron, 2007)

(untitled) - Yang, Y.; Lu, C.; Zhong, W. (ARKIVOC, 2015)

(untitled) - Browne, D. L.; Taylor, J. B.; Plant, A.; Harrity, J. P. A. (J. Org. Chem., 2009)

Cambridge Structural Database and Cambridge Structural Database system, Version 5.37 (Cambridge Crystallographic Data Centre, 2015)